A cross-sectional study: farmer’s perceptions, practices, and knowledge (PPK) on antimicrobial drug (AMD) and antimicrobial drug resistance (AMDR) at rural households in selected areas of Cumilla district, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
In response to unwise and inappropriate antimicrobial drug (AMD) use, antimicrobial drug resistance (AMDR) is rising globally. The present research was performed to find out and evaluate the perceptions, practices, and knowledge (PPK) of the farmers regarding AMD use and AMDR propagation in rural households. The study was conducted using a pre-tested questionnaire upon 200 respondents with a duration of 5 months in selected areas of Cumilla district, Bangladesh. The correlation analysis showed a significant (p